Development of Interactive Web-Based Learning Media with the Discovery Learning Model to Increase Student Learning Motivation in Object Oriented Programming XI Vocational High Schools - Mustaqim, M. Fazal (Universitas Negeri Malang, 2023)
Students have difficulty understanding object-oriented programming material. Because the learning process carried out still uses the lecture method and the learning media used in the form of PowerPoint and even textbooks, resulting in a lack of understanding and a lack of student learning motivation. Other problems arise such as drowsiness due to boring learning, and difficulty understanding due to lack of interaction between students and teachers. Today's technology that can support the learning process in solving these problems is an interactive web. This study uses the Hannafin and Peck development model which goes through 3 phases, namely (1) needs analysis, (2) design, and (3) development and implementation. Data collection techniques were carried out through observation and questionnaires. The learning media developed is in the form of an interactive web application with a discovery learning model that contains learning and evaluation videos. The results of the feasibility analysis of learning media obtained the results of media expert validation of 96.3 percent, material expert validation of 93 percent, and group trials of 85.4 percent. The results of the analysis of all feasibility data obtained an average of 91.6 percent with the qualification